Analisis Pengukuran Kinerja Perbankan Syariah dengan Menggunakan Metode Angels (Studi Kasus pada Bank Syariah Indonesia KCP. Medan Ringroad) - Kurniawati, Endang; Imsar; Harahap, Rahmat Daim (Jurnal EMT KITA, 2023)
In assessing the performance of Islamic banks, it is not only seen from their financial reports, but also based on the concept of IMAN (Islamic values-based performance assessment), which is the embodiment of the Islamic values dimensions, namely: ibadah (worship), muamalah (transactions), amanah (trustworthiness), and ihsan (excellence). The assessment system for the health of Islamic banks referred to here is ANGELS. ANGELS is an acronym for Amanah management, non-economic wealth, Give out, Earnings, Capital and assets, Liquidity and sensitivity to market, and socio-economic wealth. Each factor of ANGELS is part of the "process," "outcomes," and "stakeholders." This study aims to analyze and assess the performance of PT. BSI KCP Medan Ringroad using the Angels Method. This research is qualitative in nature and the data is obtained through interviews with several sources from PT. BSI KCP Medan Ringroad. Secondary data can be obtained from the financial statements of PT. BSI KCP Medan Ringroad. The data analysis technique used is observation and interviews. The data analysis includes data reduction, data presentation, and conclusion drawing. The results of this study indicate that PT. BSI KCP Medan Ringroad is considered healthy, as evidenced by the Angels method in measuring the performance and health level of the bank, which shows good results.